1979
DOI: 10.3177/jnsv.25.103
|View full text |Cite
|
Sign up to set email alerts
|

Comparative susceptibility of starch granules of double- and triple-mutants containing Amylose-extender, waxy, sugary-1, sugary-2 and dull genes of maize inbred OH43 (Zea mays L.) to amylase.

Abstract: SummaryStarch granules were prepared from 14 double-and 26 triple-mutants containing amylose-extender (ae), 14 double-and 18 triple -mutants containing waxy (wx), 15 double-and 20 triple-mutants containing sugary-1 (su1), 13 double-and 23 triple-mutants containing sugary-2 (su2), and 14 double-and 19 triple-mutants containing dull (du) of maize inbred Oh43 (Zea mays L.). The relative susceptibilities of these starch granules to fungal glucoamylase were determined and the starch granules were examined by scanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
1

Year Published

1980
1980
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 6 publications
(12 reference statements)
0
3
1
Order By: Relevance
“…The susceptibility to fungal glucoamylase attack of a range of mutant maize starch granules from inbred line Oh43 was investigated by Fuwa et al (1979). In contrast to our results, they found that the endosperm mutations duwx and aeduwx were highly digestible.…”
Section: Hydrolysis Of Granular Starches With α-Amylasecontrasting
confidence: 90%
See 3 more Smart Citations
“…The susceptibility to fungal glucoamylase attack of a range of mutant maize starch granules from inbred line Oh43 was investigated by Fuwa et al (1979). In contrast to our results, they found that the endosperm mutations duwx and aeduwx were highly digestible.…”
Section: Hydrolysis Of Granular Starches With α-Amylasecontrasting
confidence: 90%
“…In combination with the wx mutation, the starch does not possess amylose and the situation is thus different. The aewx granules are also of B-type crystallinity Seib 1995, Jane et al 1999) but were reported to be susceptible to amylase like most other wx combinations with A-type crystallinity (Fuwa et al 1979). In triple combination with the du and wx mutations, B-type crystallinity was reported from inbred W64A (Shi and Seib 1995).…”
Section: Hydrolysis Of Granular Starches With α-Amylasementioning
confidence: 99%
See 2 more Smart Citations